Exploring the drivers of impulsive buying in e-commerce: the role of hedonic motivation, shopping lifestyle, and positive emotions as mediation - Azizah, Nurifa Laksmitasari; Fauzi, Muhammad (Institute of Computer Science (IOCS), 2024)
All forms of products sold on E-commerce have their own risks in the form of goods that do not match the wishes of the community, slow delivery and lack of buyer response. Behind all that, fashion products on e-commerce are always in demand by consumers. Thus, fashion becomes a product that is in great demand in Indonesia, and therefore the purpose of this research is as a recommendation for retail behavior in e-commerce to start a fashion business, because Indonesian society has the character of impulse buying with the principles of hedonic motivation and shooping lifestyle in fashion products. Research data uses primary data. The research population chosen was consumers who impulsively bought fashion products in e-commerce, with a sample of 140 respondents in this study. The results obtained by this research are hedonic motivation, shopping lifestyle and positive emotions which have a positive and significant relationship to impulsive buying. Meanwhile, positive emotions themselves are also influenced positively and significantly by hedonic motivation and shopping lifestyle. The mediation results from positive emotions provide a significant relationship between the influence of hedonic motivation and shopping lifestyle on impulsive buying